The Nineveh 5 pottery at Tell Lashkr (analytic and technical study) - Abdullah Bakr Othman; Abas Ali Mahmood (QALAAI ZANIST SCIENTIFIC JOURNAL, 2023)
The pottery of Nineveh 5 is considered one of the most beautiful ‎pottery in Mesopotamia, the ‎period dating back to the beginning of ‎the third millennium B.C and contemporary to the period ‎of Jamdet ‎Nasr. This type of pottery was discovered for the first time in the ‎fifth layer of the city of Nineveh, in a different ‎ manner from ‎previous periods. The north of Mesopotamia is a country ‎rich of ‎this kind of pottery, which was discovered in most of these sites. ‎The Tell Lashkar, which ‎is located East of the city of Erbil, in ‎which huge numbers of Nineveh‎ ‎5‎ pottery were discovered ‎in ‎archaeological layers‎. The types that were previously discovered ‎in other areas, and the same ‎quality that was discovered in Tell ‎Lashkar. Through this research, we shed light on important ‎topics ‎such as (taking samples and shapes (all discovered types)), the ‎characteristics of Nineveh‎ 5 ‎pottery in Tell Lashkar, the types of ‎used clay, how to make and its stages). We have carefully ‎‎classified all the discovered types of pottery from this period and ‎are studying them carefully. ‎And from the types of used clay, ‎through our study we chose three types of clay and in their ‎‎characteristics, we talked about the type of used common pottery.‎